Extreme NXT : extending the LEGO® MINDSTORMS® NXT to the next level - Gasperi, Michael (Technology in action series., 2007)
"LEGO Mindstorms NXT is a product that allows anyone to build complex inventions, but there are limits to what you can do with what comes inside the box. This book shows you how to extend the NXT to the next level, with more than 25 projects that range from a simple light switch to a cool magic wand that writes words in thin air. The projects are explained with easy step-by-step instructions, and whether you're a novice or an expert, you'll be able to construct them successfully. A tutorial on breadboard construction and soldering is also included."--Jacket